Tailored interactive multimedia computer programs to reduce health disparities: Opportunities and challenges - Jerant, Anthony; Sohler, Nancy; Fiscella, Kevin; Franks, Becca; Franks, Peter (Patient Education & Counseling, 2011)
Objective: To review the theory and research evidence suggesting that tailored interactive multimedia computer programs (IMCPs) aimed at optimizing patient health behaviors could lessen socio-demographic health disparities.Methods: Selective critical review of research regarding IMCPs tailored to psychological mediators of behavior and their effects on health behavior and outcomes among socio-demographically disadvantaged patients.Results: Tailored IMCPs can address patient factors (e.g. language barriers, low self-efficacy) and buffer provider (e.g. cognitive bias) and health system (e.g. office visit time constraints) factors that contribute to poor provider-patient communication and, thereby, suboptimal health behaviors. Research indicates disadvantaged individuals' interactions with providers are disproportionately affected by such factors, and that their behaviors respond favorably to tailored information, thus suggesting tailored IMCPs could mitigate disparities. However, no randomized controlled trials (RCTs) have examined this question. The optimal design and deployment of tailored IMCPs for disadvantaged patients also requires further study.Conclusion: Preliminary research suggests tailored IMCPs have the potential to reduce health disparities. RCTs designed expressly to examine this issue are warranted.Practice Implications: Many socio-demographic health disparities exist, and there is a dearth of proven disparity-reducing interventions. Thus, if tailored IMCPs were shown to lessen disparities, the public health implications would be considerable.